Anti-SARS-COV-2 antibodies Amongst Asymptomatic Healthcare Workers and students of Tertiary Care hospital and Medical School in Pakistan - Jaleel, Anila; Asim, Samar; Namoos, Kiran; Uppal, Sadaf; Jaleel, Shahila; Shabbir, Waqas; Khursheed, Rukhhan (American Journal of Health, Medicine and Nursing Practice, 2021)
Introduction: Coronavirus emerged as a pandemic in 2019 with the SARS COV 2 virus infecting people worldwide. Although PCR successfully detected symptomatic patients, asymptomatic patients remained undetected due to limitation of resources. The objective of the study was to determine the prevalence of IgM and IgG antibodies in the faculty, staff, and MBBS students in Medical school and tertiary care hospital, Pakistan. Material and Methods: A cross-sectional study was conducted on 500 asymptomatic healthy subjects, from September to December 2020 in Biochemistry department Shalamar Medical and Dental College (SMDC). Rapid antibody test was used to determine the presence of IgM and IgG antibodies in the subjects. Those found IgM positive were validated by COVID 19 detection by Polymerase Chain Reaction. Results: Anti-SARS-COV 2 antibodies was observed in 19.6 % of 500 asymptomatic subjects. Significant reactive cases were identified in hospital staff (27.5%) compared to hospital faculty (23.4%), medical students (21.4%), college faculty (6.12%) followed by college staff (3.06%). Significant reactive cases (47.9%) were identified in middle age group i.e. between 31 to 45 years. IgG was more prevalent than IgM and 2% of the subjects showed coagulation disorders who were both IgG and IgM positive. Conclusion: Prevalence of 19.6% of Anti-SARS-COV 2 antibodies was observed in asymptomatic subjects. Prevalence was more in males, people in the middle age group i.e. 31 to 45 years and in hospital staff and faculty. Recommendations: Based on the study it is recommended that Rapid COVID 19- SRAC-2 antibody test, which is cost effective and rapid method may be used to detect the COVID 19 in developing countries with limited resources.